The Role of Formal and Informal Structures In Shaping the Corporation's Relational Capital = Rola struktur formalnych i nieformalnych w kształtowaniu kapitału relacyjnego przedsiębiorstwa - Haber, Lesław H. (Zielona Góra: Faculty of Economics and Management Press)
The paper presents the origin of the term of 'relational capital' by reference to such previous management systems as human relations, organizational culture, or human resources management. At the same time, the author indicates the significance of relational capital in the recent conceptions associated with the treatment of management as a process. On that background, the roles of formal and informal structures in shaping relational capital are discussed, marking both positive and negative influence of such capital in the corporate management system.
Keywords: kapitał relacyjny; system zarządzania; struktury formalne; struktury nieformalne; aspekty pozytywne kapitału relacyjnego; aspekty negatywne kapitału relacyjnego; Relational capital; management systems; formal structures; informal structures; positive aspects of relational capital; negative aspects of relational capital